Model permainan serius warisan budaya tidak ketara berasaskan pengetahuan ontologi - Wan Malini binti Wan Isa
Cultural heritage shapes the self-identity of an individual and society. However, the current younger generation is less interested in cultural heritage due to globalization and social change. Serious games have great potential in disseminating knowledge of cultural heritage. However, the development of serious games for intangible cultural heritage is still limited because knowledge of intangible cultural heritage, especially brassware craft, belongs to and is stored only in the memory of the practitioners. Serious game design for existing intangible cultural heritage does not emphasize resource and content design aspects for games. Hence, the development of games for intangible cultural heritage should take into account the knowledge possesses by the practitioners. Therefore, this study aims to develop a serious game model for intangible cultural heritage based on ontological knowledge. The objectives of this study are to design an Ontology Knowledge-Based Intangible Cultural Heritage Serious Game Model (PS- Warisan Model), develop an intangible cultural heritage knowledge base and validate the model through development and evaluation of serious game prototype (PS-Tembaga Prototype). The methodology consists of the model construction method, which involves the component analysis and model design phases and the model validation, which includes the prototype development and the evaluation phases. The component analysis phase involves literature review, preliminary research and brassware craft knowledge acquisition. The model design phase comprises the development of the model, the design of serious game and the knowledge base using Ontology Development 101 (OD101) method. In the prototype development phase, the model is implemented in the game prototype. The [mal phase is the game prototype evaluation by target users. Results of the effectiveness evaluation showed that the game prototype is effective in conveying knowledge to players. The post-test scores increased by 52% compared to pre-test scores. Paired Sample T- Test results showed that there is a significant difference between pre-post test scores (p=O.OOO, 0.=0.05). The playability and usability evaluation indicates that the prototype has good playability and usability. The results of the self-identity test showed that the game could improve the self-identity of players. Overall, the evaluation results indicate that the PS- Warisan Model can be used effectively in designing and delivering game content. The PS-Warisan Model can be implemented in the game design for other intangible cultural heritage. The contributions of this study are the PS-Warisan Model, brassware craft knowledge base, game assets and game interface design.